Identification and Validation of Key Biomarkers in the Proximal Aqueous Humor Outflow Pathway - Rong Du; Enzhi Yang; Madison Clark; Ningli Wang; Yiqin Du (Current Issues in Molecular Biology)
Glaucoma is a leading cause of irreversible blindness, with elevated intraocular pressure (IOP) as the most important risk factor. The trabecular meshwork (TM) and Schlemm’s canal are the main components of the proximal aqueous humor outflow pathway. Their dysfunction is a major contributor to IOP elevation. This study aims to identify and validate key biomarkers for TM and Schlemm’s canal endothelial (SCE) cells. A Microarray was performed on characterized human TM and SCE cells to analyze their transcriptome profiling. Differentially expressed genes (DEGs) were identified and cross-referenced with published single-cell RNA sequencing (scRNA-Seq) datasets to ensure cell-specific relevance. Further validation was performed using qPCR and re-confirmed on the scRNA-seq datasets. One-way ANOVA was used for statistical analysis, and p < 0.05 was considered significant. The Microarray revealed 341 DEGs, with TM cells enriched in metabolic and signaling pathways and SCE cells enriched in adhesion, immune, and morphogenesis-related processes. Cross-referencing with scRNA-Seq data refined the list of candidate biomarkers, and qPCR confirmed the significant gene expression differences between TM and SCE cells. CTTNBP2 and MGARP were identified as TM cell markers. JAM2, PODXL, and IFI27 are new SCE cell biomarkers. The validated biomarkers offer insights into glaucoma pathophysiology and lay the groundwork for targeted therapies.